Asymmetric scapuloperoneal phenotype of MATR3-related distal myopathy: case series - Murtazina, Aysylu; Subbotin, Dmitrii; Kuchina, Anna; Gilvanova, Olga; Degterev, Daniil; Shchagina, Olga; Cherevatova, Tatiana; Bulakh, Maria; Sherstyukova, Darya; Ryzhkova, Oksana; Kurushina, Olga; Skoblov, Mikhail; et al. (Frontiers in Genetics, 2024)
Recent research has sparked a discussion on the spectrum of diseases linked to the MATR3 gene associated with amyotrophic lateral sclerosis and distal myopathy with vocal cord and pharyngeal weakness (VCPDM). To date, fewer than 50 cases of VCPDM have been reported in the literature. We aim to build upon the work of previous researchers by gathering additional information about VCPDM. In this study, we present six patients from four unrelated families affected by VCPDM. Our observations include patients exhibiting both the typical phenotype associated with MATR3-related distal myopathy and rare symptomatic manifestations of the disease. Notably, two cases presented with an asymmetric scapuloperoneal phenotype, leading in one case to an initial misdiagnosis of facioscapulohumeral muscular dystrophy.